A case of hemophagocytic lymphohistiocytosis caused by an Epstein-Barr virus infection, presenting with unremitting fever and rash - Seong-Beom Oh; Chan-Young Koh (Pediatric Emergency Medicine Journal, 2019)
Hemophagocytic lymphohistiocytosis (HLH) is a hyperinflammatory syndrome caused by excessive activation of lymphocytes and macrophages, leading to cytokine storm. Infection-associated HLH is most common, and Epstein-Barr virus is the leading triggers. Quick diagnosis is essential for starting the treatment before irreversible damage. We report a case of 16-year-old boy who presented with unremitted fever, jaundice, and erythematous maculopapular rash all over the body. Investigations showed thrombocytopenia, hyperferritinemia, hypertriglycemia, and the bone marrow biopsy showed hemophagocytosis. Epstein-Barr virus antibody was positive. He responded to chemotherapy as per the HLH-2004 protocol and supportive treatment, and was discharged without complication on day 17.